Evaluation of Psychotherapy with PTSD clients : A longitudinal Study - Ljubotina, Damir (Array, 2005)
517 clients with war trauma experience were included in a longitudinal study in several countries. Here we present results for 231 clients included in psychotherapy in Croatia. The whole sample consists of 79% of war veterans and 21% of refugees. All clients were interviewed at baseline and followed up after 3 and 12 months. The main goal of the study was to assess treatment outcomes in people included in formal psychotherapy and factors related with treatment outcomes. Measures of treatment outcome included measures of PTSD symptoms (semi-structured interview and scales), level of traumatic experience, 9 dimensions of general psychopathology, socio-demographic data, quality of life, personality traits, social acknowledgment, wishes for compensation, coping strategies, physical health, motives and expectations concerning treatment, costs of health service utilisation and other support, client-therapist relationship, patients experiences with the given treatment, current stress, migration stressors and acculturation for refugees. According to the used List of traumatic events war veterans and refugees don't differ significantly in the number of stressful and traumatic events. On the baseline, war veterans have significantly higher levels of intrusion symptoms, avoidance and hyper arousal according to self-reported measures, but the semi-structured interview showed no significant differences between war veterans and refugees. Also war veterans show significantly higher intensity of symptoms on all general dimensions of psychopatology (depression, anxiety, interpersonal sensitivity, hostility, etc.) with an exception of somatisation were we found no difference. They also used more maladaptive coping strategies (avoiding people, expression of anger toward persons not responsible for their problems). Preliminary results of the follow-up study show significantly lower levels of symptoms in the first three months of therapy, but only for refugees and no changes in the war veterans sample. For the 3-12 months interval we found no significant improvement for both samples. The authors discuss the results in the light of psychosocial and political contexts that form the posttraumatic environment for therapy.